2013
DOI: 10.1111/jgh.12304
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B surface antigen quantification as a useful assessment for significant fibrosis in hepatitis B e antigen‐positive hepatitis B virus carriers

Abstract: Serum qHBsAg-based simple tests, especially GqHBsR, can accurately and specifically identify significant fibrosis in treatment-naïve HBeAg-positive HBV carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…ΔThe disease spectrum of some studies [11], [17], [19]–[21], [24], [26][28] were not in good accordance with our study, thus they were excluded for sensitivity analysis.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…ΔThe disease spectrum of some studies [11], [17], [19]–[21], [24], [26][28] were not in good accordance with our study, thus they were excluded for sensitivity analysis.…”
Section: Resultsmentioning
confidence: 89%
“…Despite this limitation, these factors were assessed in meta-regression for exploring sources of heterogeneity. The disease spectrum of 9 studies [11], [17], [19]–[21], [24], [26][28] were not in good accordance with our study and were excluded for further sensitivity analysis. Specifically, three of these studies [20], [24], [27] focused on patients with limited ALT (normal or less than 2× upper limit of normal), one focused on Hepatitis B virus e antigen (HBeAg)-positive patients [28], one focused on HBeAg-negative patients [26], one defined the urea nitrogen limitation when collecting samples [11], one included patients after therapy [19], one only included inpatients [17], and one did not describe the objective of the study clearly [21].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Demiroren et al conducted a study on 56 HBeAg positive patients receiving interferon alpha 2b treatment and found no meaningful relationship between qHBsAg level and fibrosis degree (30). Contrary to what was noted in that study, it was demonstrated that qHBsAg levels specifically identified significant fibrosis in treatment-naive HBeAg-positive HBV carriers in another study conducted with a larger patient group (31). In another investigation carried out by Farnik et al with analogs of nucleotides and nucleosides, the M-30 apoptosis epitope and its quantitative levels before and after treatment were evaluated, and a significant decrease in HBV DNA parallel to qHBsAg was observed at the 24th week of treatment.…”
mentioning
confidence: 76%